Synthesis and Study of the Trypanocidal Activity of Catechol-Containing 3-Arylcoumarins, Inclusion in β-cyclodextrin Complexes and Combination with Benznidazole - Mera-Adasme, R (Elsevier B.V., 2022)
American trypanosomiasis or Chagas disease is caused by the protozoan parasite Trypanosoma cruzi, and is considered a neglected disease, being an important problem for public health. Benznidazole (BZN) is the drug used to treat the disease. However, it has limited efficacy and adverse side effects. Therefore, the development of new therapeutic alternatives is necessary. In this work, the trypanocidal activity and cytotoxicity of a series of catechol-containing 3-arylcoumarins, their combination with BZN, and the inclusion in β-cyclodextrins (β-CDs), were evaluated. The results obtained showed that the entire series has moderate trypanocidal activity on the trypomastigote form of the parasite, being the 3-(4′-bromophenyl)-6,7-dihydroxycoumarin (8) the most active compound (IC50 = 34 μM) and the most cytotoxic in Vero cells (IC50 = 162 μM) as well. By forming the inclusion complex 8-β-CDs, the trypanocidal activity and cytotoxicity decreased. In addition, the formation of inclusion complexes increased the solubility. The possible mechanism of action of 8 was evaluated and proved to be through the generation of oxidative stress. The combination with BZN presented a synergistic effect on the trypanocidal activity, reducing the necessary dose of BZN. The presence of a catechol in the studied scaffold seems to modulate the trypanocidal activity, and the combination of drugs proved to be a promising alternative strategy for treating the disease. © 2021 The Authors